Penguatan Penyusunan Judul Artikel Ilmiah Pada Civitas Akademika Universitas Bhakti Kencana Kampus Kendal - Slamet Utomo; Lucky Restyanti Wahyu Utami; Rose Malinda Andamari Wahyu Utami (Universitas Muria Kudus, 2026)
The purpose of the strengthening activities carried out at Bhakti Kencana University, Kendal Campus is to determine the level of ability and knowledge of the academic community regarding the preparation of scientific article titles. Based on the results of the strengthening activities carried out, it is known that the respondents are lecturers and students of Bhakti Kencana University, Kendal Campus, all of whom are women. The conclusion obtained is that there is an increase in each aspect including the aspect of creating article titles that contain the main topic to be discussed has increased to 91.7%, the aspect of creating unique and interesting article titles has increased to 91.7%, the aspect of knowledge about the number of words in the article title has increased to 100% and the aspect of knowledge about article titles that reflect the content and purpose of the article has increased to 100%.